Techno-economic analysis of Dimethyl Ether production using Oil Palm Empty Fruit Bunches as feedstock – a case study for Riau. (June 2019) - Parbowo, H S; Ardy, A; Susanto, H
Abstract: The increase of Liquid Petroleum Gas (LPG) import in Indonesia made the government promote Dimethyl Ether (DME) as partial substitution of LPG as written in the General Planning of National Energy (RUEN) 2017. DME can be produced from biomass which abundantly exists in Indonesia. Such biomass is especially oil palm empty fruit bunches (EFB) that consist of 49.07% C, 6.48% H, 0.70% N, 38.29% O, and 5.36% Ash. Techno-economic analysis of this bio-DME production plant was conducted based on literature data. The direct synthesis of DME was applied in this study, instead of using methanol as an intermediate product. Result calculated from mass and energy balance simulation was 4.1 EFB/DME. Thus, 1, 090 ton per day of DME can be produced from EFB with a collecting radius of 100 km in Riau Province. Assuming 20 years plant operation with DME selling price of IDR 145, 000/12-kg-LPG-equivalent and EFB price of 300 IDR/kg, economic evaluation showed that this business was economically feasible with 10.08% IRR generated. The CAPEX of this plant was 990.4 million USD and the OPEX was IDR 7, 143 IDR/kg-LPG-equivalent. DME production from EFB will give the positive economics and environmental effects. Therefore, support and synergy from government, industries, and academics are needed to realize this business.